Impulse Buying Behavior in E-Commerce Users: A Study of Consumptive Society and Islamic Consumption Ethics in a Sociological Perspective - Ahmed Fernanda Desky; Muhammad Jailani; Aulia Kamal (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The development of digital technology has changed the consumption patterns of people, including Muslim students, who are increasingly actively using e-commerce platforms. This study aims to analyze the influence of social behavior, e-commerce use, and Islamic consumption ethics on impulse buying behavior among Muslim students. The method used is a mixed method with a sequential explanatory approach, starting with a quantitative survey of 100 students of the Universitas Islam Negeri Sumatera Utara and continuing with in-depth interviews and focus group discussions to explore quantitative results qualitatively. Linear regression analysis showed that social behavior (r = 0.287, p < 0.001) and e-commerce use (r = 0.127, p < 0.001) had a significant influence on impulse buying. In contrast, Islamic consumption ethics did not show a statistically significant effect (r = 0.009, p = 0.358). The F test indicated that all three independent variables simultaneously had a significant effect on impulse buying. Qualitative findings reveal that, although Islamic values continue to be a consideration in the consumption of essential products, they are not the sole influence. Digital habitus and economic, social, cultural, and symbolic capital influence impulse buying behavior within the framework of Pierre Bourdieu's theory. The integration of technology and consumer culture in the digital era also influences spontaneous purchasing decisions, showing the duality between ethical values and consumptive desires. The impulse buying behavior of Muslim students is not only influenced by needs, but also by the social construction and digital lifestyle that shapes the identity of its consumers.